2011 IEEE Applied Imagery Pattern Recognition Workshop (AIPR) 2011
DOI: 10.1109/aipr.2011.6176373
|View full text |Cite
|
Sign up to set email alerts
|

Real-time eye tracking using a smart camera

Abstract: International audienceReal-time eye and iris tracking is important for hands-off gaze-based password entry, instrument control by paraplegic patients, Internet user studies, as well as homeland security applications. In this project, a smart camera, LabVIEW and vision software tools are utilized to generate eye detection and tracking algorithms. The algorithms are uploaded to the smart camera for on-board image processing. Eye detection refers to finding eye features in a single frame. Eye tracking is achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The full-duplex form allows communication in both directions, which results in faster transmission. The computer has a Pentium 4 2.26GHz processor, an on-board 64 MB graphics card and 1.25 GB RAM 15 . LabVIEW desktop interface is used to communicate with the smart camera.…”
Section: Hardware Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-duplex form allows communication in both directions, which results in faster transmission. The computer has a Pentium 4 2.26GHz processor, an on-board 64 MB graphics card and 1.25 GB RAM 15 . LabVIEW desktop interface is used to communicate with the smart camera.…”
Section: Hardware Setupmentioning
confidence: 99%
“…The main component of the eye tracking system is a NI 1762 smart camera with a Computar 12 mm lens and the Gigabit Ethernet interface 14,15 . The smart camera has dual processors.…”
Section: Hardware Setupmentioning
confidence: 99%
“…In preprocessing phase, we need to remodel color image into grayscale image, which applied in haar method as well [10]. So that, it need to transform from RGB image into grayscale image.…”
Section: Grayscaling Imagementioning
confidence: 99%
“…Most of the existing software indeed requires basic programming skills in languages such as Python, C/C++ and Matlab. Previous research has reported the development of an eye-detection system from a smart camera using a visual programming environment called LabView (Mehrubeoglu et al, 2011). However, the data analysis stage was not addressed and the code was not made public.…”
Section: Introductionmentioning
confidence: 99%